Chinese Attitudes toward Intellectual Property Rights-Change and Continuity - Hai, Heidi (Ge); Dutton, Peter A.; Cohen, Jerome A. (American Journal of Trade and Policy, 2022)
Intellectual property has been central to Sino-US disputes in the past decades. The US government has taken various measures to compel China to enforce IP rights (IPR) protection in conformity with what would be acceptable by US standards, only to find differences persisting and these IPR disputes far from resolved. To better understand the tension between China and the US over IPR protection, this note provides a historical analysis of China’s IPR development from Late Qing to today, focusing on the changes and continuities in Chinese attitudes toward IPR across different periods. Without indigenous concepts of IPR, China was forced to accept western standards at a time of military and political weakness and has consequently remained vigilant against foreign domination in this field. However, China also gradually developed a genuine appreciation for modern IPR to the degree that would benefit China's economic development and status in the global community. A normative judgment on China's IPR protection would frustrate efforts at dispute resolution by assuming US standards of IPR protection as universally ideal. As China and the US continue to cooperate in trade and technology, mutual understanding and appreciation of a shared set of IP standards would be essential.
Keywords: Intellectual Property; China, Sino-US; IPR; Copyright; Trademark; Patent; Legal History; International Law